The Natural Products as Hydroxymethylglutaryl-Coa Reductase Inhibitors - Gulcan, Hayrettin Ozan; Yigitkan, Serkan; Orhan, Ilkay Erdogan (Bentham Science Publ Ltd, 2019)
High cholesterol and triglyceride levels are mainly related to further generation of life-threating metabolism disorders including cardiovascular system diseases. Therefore, hypercholesterolemia (i.e., also referred to as hyperlipoproteinemia) is a serious disease state, which must be controlled. Currently, the treatment of hypercholesterolemia is mainly achieved through the employment of statins in the clinic, although there are alternative drugs (e.g., ezetimibe, cholestyramine). In fact, the original statins are natural products directly obtained from fungi-like molds and mushrooms and they are potent inhibitors of hydroxymethylglutaryl-CoA reductase, the key enzyme in the biosynthesis of cholesterol. This review focuses on the first identification of natural statins, their synthetic and semi-synthetic analogues, and the validation of hydroxymethylglutaryl-CoA reductase as a target in the treatment of hypercholesterolemia. Furthermore, other natural products that have been shown to possess the potential to inhibit hydroxymethylglutaryl-CoA reductase are also reviewed with respect to their chemical structures.
Keywords: HMG-CoA reductase; enzyme inhibition; hypercholesterolemia; natural products; statins; cholesterol